Chinese Macrosecuritization China's Alignment in Global Security Discourses - Vuori, Juha A. (Routledge New Security Studies, 2024)
This book provides a holistic picture of Chinese global security discourses, with a focus on macrosecuritizations. The work examines how the People's Republic of China (PRC) has aligned itself within global security discourses. This is approached through the theory of securitization, specifically by using the notion of macrosecuritization as the lens for its analysis. The book offers the first full account of Chinese macrosecuritization discourses and alignments, and it aims to discern what security speech with referent objects such as humanity, civilization, or nature has done in the domestic and international politics of China. Specifically, the work focuses on the discourses of the Cold War, anti-nuclear weapons, climate change, and the Global War on Terror, which have all been postulated in the literature as macrosecuritizations. In addition, it examines discourses with global referent objects that have been put forth by the PRC so that we can see whether its proposals for global security governance take the form of, or are legitimated through, macrosecuritization. The overall argument in the book is that the way contemporary China uses macrosecuritization discourses provides for ontological security as its position in relation to other major powers is undergoing transformation, by allowing it to maintain a consistent narrative of its international self that abides by its own set of moral values and sense of worth. This book will be of interest to students of critical security studies, Chinese politics and International Relations.